Blended learning challenges of EFL undergraduate students: Student learning experience in an AI-integrated ESP course - Pimsiri Taylor (Studies in English Language and Education)
Blended learning can facilitate ESP learning, yet challenges in AI-integrated ESP learning are largely unexplored. This study aims to investigate the blended learning challenges of EFL undergraduate students from the perspective of student learning experience in an AI-integrated ESP course. The participants were 57 Thai mixed-level undergraduate students studying English for economics at a public university in Thailand. Using a mixed-method approach, student data were collected and analysed using Microsoft Teams learning analytics and triangulated with a questionnaire and focus group interview data. Study results showed similarities and differences in students’ blended learning challenges in the diverse target participants. Participants generally viewed technological and online learning aspects as the least challenging, in contrast with social aspects as the most challenging, followed by motivation and willingness to participate in the blended learning ESP course. Despite students’ academic achievement, data revealed students’ negative emotions and negative blended learning experiences amongst higher-proficiency students, but lower level of blended learning challenges due to easy learning tasks and lack of teacher support for more advanced language skills. In contrast, lower-proficiency students recorded more positive emotions and blended learning experiences but a higher level of blended learning challenges. Despite lower-level English, lower-proficiency students experienced teacher support both in using AI and ESP. The study highlights the importance of teacher support, which fulfils the incomplete roles of AI in ESP blended learning, and calls for a reconceptualisation of blended learning challenges. Implications for pedagogy and research on AI-integrated blended learning in ESP contexts are provided.